Child Survival Dynamics in Nigeria: Is the 2006 Child Health Policy Target Met? (Nigerian Journal of Health Sciences, 2023)
Background: The childhood mortality rate in Nigeria continued to remain high. Unfortunately, information on the regional trajectories, progress, and sociodemographic determinants of childhood mortality in Nigeria are not readily available. The objectives of this study are to describe the childhood mortality trajectory in Nigeria, assess progress made toward achieving the 2006 child health policy targets, and determine the peculiar factors associated with childhood mortality in Nigeria regions. Materials and Methods: Birth history data from the Nigeria Demographic and Health Surveys for 1990, 2003, 2008 and 2013 were analysed. Childhood mortality levels were derived using indirect demographic techniques. Locally weighted scatterplot smoothing technique was employed to ascertain the childhood mortality trajectory. Weibull frailty models were fitted to determine the influence of unmeasured variables and factors associated with childhood death in each region. Results: Childhood mortality stagnated at 207/1000 live births until the year 2000, after which there was a linear decline to 137/1000 live births in 2010 at an annual rate of 4.91% (confidence interval: 4.52–5.29). The rate of decline was least in the South West (2.97%) and highest in the North Central (7.40%). Multivariate analysis revealed that unmeasured community factors played significant roles in North East and North West. Birth interval < 24 months, multiple births, and young maternal age were risk factors across all regions. Conclusions: Nigeria child survival dynamics differ between the Northern and Southern regions and rural and urban locations. Only the North Central and South-South regions are on course to achieve the 2006 targets for under‑five mortality reduction. Multiple birth, short birth intervals, and young maternal age at child’s birth were risk factors for childhood mortality in the six geo-political regions in Nigeria